Detection of trapped molecular O2 in a charged Li-rich cathode by Neutron PDF. Issue 1 (16th December 2021) - House, Robert A.; Playford, Helen Y.; Smith, Ronald I.; Holter, Jennifer; Griffiths, Ian; Zhou, Ke-Jin; Bruce, Peter G.
Abstract : Direct structural evidence for the presence of trapped molecular O2 in charged Li-rich O-redox cathodes from neutron total scattering data. Abstract : Oxidation and reduction of the oxide ions in the bulk of cathode materials is a potential route towards increasing the energy density of Li-ion batteries. Here, we present neutron PDF data which demonstrates the presence of short 1.2 Å O–O distances in a charged O-redox cathode material, corresponding to the bond length of molecular O2 . This was achieved by collecting our data close to absolute zero (2 K), suppressing thermal motion which may have obscured detection by PDF previously. This direct detection of molecular O2 trapped in the material by diffraction complements the X-ray spectroscopy studies by e.g. RIXS while avoiding issues of possible beam damage as well as being a bulk average technique.